An agency-based model of executive and metacognitive regulation - Tomasello, Michael (Frontiers in Developmental Psychology, 2024)
In the context of agentive decision making and action, both executive and metacognitive processes serve self-regulatory functions—just on different hierarchical tiers. In the agency-based model proposed here executive processes monitor and control action and attention from an executive tier of operation, and metacognitive processes monitor and control those executive processes from a second-order metacognitive tier of operation-both with the function of facilitating effective and efficient behavioral decisions. Each is best conceptualized as comprising three key components: (i) what is regulated, (ii) how, via what processes, is it regulated, and (iii) where, in what cognitive workspace, is it regulated—either in individual or in shared agencies. Developmentally, evidence is presented that executive processes for regulating both individual and joint agencies emerge only after 9–12 months of age, and metacognitive processes for regulating both individual and collective agencies emerge only after 3–4 years of age. Cognitive flexibility, as an important outcome, derives from the child's attempts to metacognitively regulate differing social perspectives within shared agencies.